Aramaic Inscriptions in the Palmyra Museum - Al-Asʿad, Khaled; Gawlikowski, Michal; Yon, Jean-Baptiste (2012)
Some sixty new Aramaic epitaphs from Palmyra are published. Most of them have been found by the Palmyra Museum in the area of the ancient city Northern wall. Before those epitaphs, several new foundation and concession inscriptions are given as well. Those data give new insights on the onomastic and the funerary sculpture of Palmyra.
Keywords: Semitic epigraphy; Palmyra/Tadmor; Ancient Syria; Aramaic epigraphy; Epitaph; onomastic